Writing history in Late Modern English explorations of the Coruña corpus - Moskowich, Isabel; Crespo García, Begoña; Puente-Castelo, Luis Miguel; Monaco, Leida Maria (John Benjamins Publishing Company, 2019)
"This volume focuses on the relationship and interaction of language and science between 1700 and 1900. It pays particular attention to English history writing in Late Modern English as compiled in the Corpus of History English Texts (CHET), a newly released subcorpus of the Coruña Corpus of English Scientific Writing. The chapters cover methodological issues, the period and the status of discipline itself, as well as pilot studies for the description of scientific discourse using CHET. They embrace topics in several linguistic fields: discourse analysis, syntax, semantics, morphosyntax. The studies take into account extralinguistic parameters of texts, such as year of publication, sex of the author, geographical provenance of authors and the communicative formats/genres to which the text sample belongs. In the particular case of CHET, the collected samples can be grouped in eight different categories and such categories, as well as the above-mentioned metadata information, can be used to search the corpus. The Corpus of History English Texts (CHET), accompanied by the Coruña Corpus Tool (CCT) purpose-designed software by IrLab, is accessible online at the Repositorio Universidade Coruña at http://hdl.handle.net/2183/21849"--